Investigation of the Effects of Titanate as Coupling Agent and Some Inorganic Nanoparticles as Fillers on Mechanical Properties and Morphology of Soft PVC - Morteza Hajian; Gholam Ali Koohmareh; Afsaneh Mostaghasi (International Journal of Polymer Science)
The effects of titanate as a coupling agent and some particulate nanoscale particles such as TiO2, CaCO3, and ZnO on thermal and mechanical properties of emulsion polyvinylchloride (E-PVC) were investigated by thermogravimetric analysis (TGA), and mechanical tests. In this research, it was found that, in the presence of nanoparticles of CaCO3, TiO2, and ZnO, the peak temperature of dehydrochlorination of E-PVC was shifted to higher temperatures, and the rate of mass loss was decreased. Also results of differential scanning calorimetry showed that the addition of nanoparticle of CaCO3, TiO2, and ZnO led to an increase in glass transition temperature. The impact strength, elastic modulus and toughness of the samples were enhanced after addition of 0–10 part of filer in hundred parts of resin (phr) nano-CaCO3, nano-TiO2, and nano-ZnO due to improvement of compatibility of the polymer and the nano-particles. Also UV and thermal stability of the samples were enhanced by means of the nanoparticles. It was found that, in the presence of titanate as coupling agent, content of additives that could be used in the composite of PVC shifts to higher amounts.